Atlantic 87/88 - Cruise No. M6 - October 28 - December 2, 1987 - Hamburg (Germany) - Abidjan (Ivory Coast) - Müller, Thomas J; Siedler, Gerold; Zenk, Walter (DFG-Senatskommission für Ozeanographie, 1988)
The first three legs of METEOR cruise No. 6 were carried out between Hamburg, Las Palmas, Dakar and Abidjan. The core programme was part of the special research programme "Warm Water Sphere of the Atlantic" at Kiel University. It included investigations of the North Atlantic subtropical gyre circulation and of mixing processes in the Cape Verde Frontal Zone. Tacer sampling was added to this programme. Furthermore, measurements were carried out to study heavy metals and petroleum hydrocarbons, and samples were collected for investigations of the oceanic particle flux, of the taxonomy and regional distribution of ichthyoplankton and of benthic communities. Air chemistry measurements were aimed at determining mixing ratios of various trace gases in the tropospheric boundary layer. The present report summarizes the goals of the investigations, the work at sea and first results. : METEOR-Berichte